Nanomedicine Approaches to Negotiate Local Biobarriers for Topical Drug Delivery. Issue 1 (14th October 2020) - Mustfa, Salman Ahmad; Maurizi, Eleonora; McGrath, John; Chiappini, Ciro
Abstract: Topical treatments have been widely adopted to address a broad range of conditions across multiple sites thanks to their convenience, versatility, and effectiveness. While bypassing systemic biobarriers and avoiding systemic side effects by delivering directly to the target tissue, topical treatments still face significant local biobarriers that limit their efficacy. The toolset available for nanodelivery systems and their inherent multifunctionality can contribute to simultaneously address otherwise intractable challenges related to barrier function evasion, drug solubility, bioavailability, pharmacokinetics, smart and sustained release, quantitative co‐delivery, and local targeting which are key to successful topical treatments. This review summarizes the outstanding challenges associated with the topical treatments of key diseases of the skin, mucosae, eyes, and ears, and highlights how nanodelivery systems are being developed to address them effectively. Abstract : Topical treatments are of high clinical value because their simplicity brings high patient compliance and satisfaction alongside limited side effects. Yet, designing effective topical drug delivery systems remains challenging, due to the efficient topical biobarriers and the complexity of combining effective delivery, local retention, and appropriate pharmacokinetics. Here the ways in which nanomaterials contribute to tackling these competing challenges is highlighted.